Interferensi Bahasa Indonesia terhadap Bahasa Bugis pada Pedagan Bugis di Pasar Rakyat Kefamenanu - Irfan Fajar Sandrang; Lenny Nofriyani Adam (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
This study aims to describe and obtain an overview of the interference of the Indonesian language to the Bugis language in the Kefamenanu People's Market. The type of research used in this research is descriptive qualitative. Data collection techniques include direct observation activities. The data analysis used is an informal technique. The results of the study show that the interference of Indonesian to Bugis language occurs in the lexical and phonological fields as well as the factor of language interference due to the habit of speakers using the local language as the first language and the existence of language contact between Indonesian and Bugis. Keywords: bugis language, indonesian language, interference